Applying Stake's Countenance Evaluation Model to Community-Based Tourism Governance: A Case Study of Pokdarwis in Pontianak City, Indonesia - Sohirah Sohirah; Iis Prasetyo (Papanda Publisher, 2026)
Community-based tourism governance in Indonesian desa wisata (tourism villages) remains underexplored, particularly regarding the organizational effectiveness of Kelompok Sadar Wisata (Pokdarwis) following national recognition. This study evaluates Pokdarwis governance at Kampong Melayu BML Tourism Village, Pontianak City — a top-50 finalist in the 2022 Anugerah Desa Wisata Indonesia (ADWI) — using Stake's (1975) Countenance Evaluation Model. Data were collected from 20 Pokdarwis members via structured questionnaires and from eight informants through semi-structured interviews, supplemented by observation and document review. Factor analysis was applied across the three Countenance dimensions: antecedents, transactions, and outcomes. Findings reveal a systematic perception–reality divergence across all three dimensions. While members self-reported 90–100% program achievement, independent observation confirmed average attainment of 70–80%. Community participation (70%) and economic impact (70%) were the weakest indicators, and vendor non-compliance with capacity-building commitments was identified as a critical governance gap. These results demonstrate that structural organizational readiness does not guarantee substantive governance effectiveness, and that member self-reports systematically overestimate program outcomes. The study contributes a novel application of the Countenance Model to community-based tourism governance evaluation, with implications for post-award audit policy in Indonesia's national desa wisata program.